Salvage high intensity focused ultrasound for residual or recurrent cervical cancer after definitive chemoradiotherapy - Zhong, Qin; Tang, Fei; Ni, Tingting; Chen, Yanping; Liu, Yuncong; Wu, Jing; Zhou, Wen; Feng, Zhiyu; Lu, Xiaokai; Tan, Shisheng; Zhang, Yu (Frontiers in Immunology, 2022)
Objective The treatment of residual/recurrent cervical cancer within a previously irradiated area is challenging and generally associated with a poor outcome. Local treatments such as salvage surgery and re-irradiation are usually traumatic and have limited efficacy. High intensity focused ultrasound (HIFU) treatment can directly ablate solid tumors without damaging neighboring healthy tissue. However, the HIFU studies for these patients are limited. Experience gained over the course of 10 years with the use of HIFU for the management of residual/recurrent cervical cancer after chemoradiotherapy is reported herein. Methods 153 patients with residual/recurrent cervical cancer in a previously irradiated field who received HIFU treatment between 2010 and 2021 were retrospectively analyzed. Adverse effects, survival benefit and factors affecting prognosis were given particular attention. Results A total of 36 patients (23.5%) achieved a partial response following HIFU treatment and 107 patients (69.9%) had stable disease. The objective response and disease control rates were 23.5% and 93.5%, respectively. The median progression-free survival (mPFS) and median overall survival (mOS) were 17.0 months and 24.5 months, respectively. Moreover, patients with lesions ≥1.40 cm before HIFU treatment and a shrinkage rate ≥ 30% after treatment had a higher mPFS and mOS, and patients with lesions ≤1.00 cm after HIFU treatment had a higher mPFS (P=<0.05). All the treatment-related adverse events were limited to minor complications, which included skin burns, abdominal pain and vaginal discharge. Conclusions HIFU treatment is likely a preferred option for cervical cancer patients with residual disease or recurrence following CRT that can safely improve the local control rate and extend survival.